A GWAS meta‐analysis from 5 population‐based cohorts implicates ion channel genes in the pathogenesis of irritable bowel syndrome. Issue 9 (19th April 2018) - Bonfiglio, F.; Henström, M.; Nag, A.; Hadizadeh, F.; Zheng, T.; Cenit, M. C.; Tigchelaar, E.; Williams, F.; Reznichenko, A.; Ek, W. E.; Rivera, N. V.; Homuth, G.; et al.
Abstract: Background: Irritable bowel syndrome (IBS) shows genetic predisposition, however, large‐scale, powered gene mapping studies are lacking. We sought to exploit existing genetic (genotype) and epidemiological (questionnaire) data from a series of population‐based cohorts for IBS genome‐wide association studies (GWAS) and their meta‐analysis. Methods: Based on questionnaire data compatible with Rome III Criteria, we identified a total of 1335 IBS cases and 9768 asymptomatic individuals from 5 independent European genotyped cohorts. Individual GWAS were carried out with sex‐adjusted logistic regression under an additive model, followed by meta‐analysis using the inverse variance method. Functional annotation of significant results was obtained via a computational pipeline exploiting ontology and interaction networks, and tissue‐specific and gene set enrichment analyses. Key Results: Suggestive GWAS signals ( P ≤ 5.0 × 10 −6 ) were detected for 7 genomic regions, harboring 64 gene candidates to affect IBS risk via functional or expression changes. Functional annotation of this gene set convincingly (best FDR‐corrected P = 3.1 × 10 −10 ) highlighted regulation of ion channel activity as the most plausible pathway affecting IBS risk. Conclusion & Inferences: Our results confirm the feasibility of population‐based studies for gene‐discovery efforts in IBS, identify risk genes and loci to be prioritized in independent follow‐ups, and pinpoint ion channels as important players and potential therapeutic targets warranting further investigation. Abstract : Irritable bowel syndrome (IBS) shows genetic predisposition, however, large‐scale, powered gene‐mapping studies are lacking. Based on questionnaire data compatible with Rome III Criteria, we selected a total of 1, 335 IBS cases from 5 independent European cohorts and performed a genome‐wide association study. We identified 7 genomic regions with suggestive signals, harboring 64 genes, and highlighted the ion channel activity as the most plausible pathway affecting IBS risk.